2005
DOI: 10.4049/jimmunol.174.12.7800
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Mouse IL-7 Receptor α Promoter by Glucocorticoid Receptor

Abstract: Expression of the IL-7R α-chain (IL-7Rα) is strictly regulated during the development and maturation of lymphocytes. Glucocorticoids (GC) have pleiotypic effects on the growth and function of lymphocytes. Although GC have been reported to induce the transcription of IL-7Rα gene in human T cells, its molecular mechanism is largely unknown. In this study, we show that GC up-regulate the levels of IL-7Rα mRNA and protein in mouse T cells. This effect does not require protein synthesis de novo, because protein syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 44 publications
3
53
0
1
Order By: Relevance
“…1, A and B). These results parallel those previously obtained using the transformed murine T cell line KKF, which responds to Dex by up-regulating IL-7R␣ protein expression (16). Dex treatment induces nuclear localization and binding of the glucocorticoid receptor transcription factor to an evolutionarily conserved region 3.5 kb upstream of the transcriptional start site of the Il7r gene (16).…”
Section: Glucocorticoids Induce Il-7r␣ Expression By Down-regulating supporting
confidence: 79%
See 1 more Smart Citation
“…1, A and B). These results parallel those previously obtained using the transformed murine T cell line KKF, which responds to Dex by up-regulating IL-7R␣ protein expression (16). Dex treatment induces nuclear localization and binding of the glucocorticoid receptor transcription factor to an evolutionarily conserved region 3.5 kb upstream of the transcriptional start site of the Il7r gene (16).…”
Section: Glucocorticoids Induce Il-7r␣ Expression By Down-regulating supporting
confidence: 79%
“…GR binds to a putative Il7r enhancer in an evolutionarily conserved sequence 3.5 kb upstream of the transcriptional start site (16). The GR site in this evolutionarily conserved sequence is 50 base pairs away from a FoxO1 transcription factor binding site, which positively regulates gene expression in both naive CD4 ϩ and CD8 ϩ T cells (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Some ␥ c chain cytokines and steroids have also been found to regulate IL-7R␣ expression (13,23,24,26). IL-7 and several other ␥ c chain cytokines induce rapid IL-7R␣ down-regulation that is transient in nature because the T cells quickly regain IL-7R␣ expression following removal from high-dose cytokine exposure (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most evidence suggests that control of IL-7R␣ expression in T cells is mediated primarily through changes in Il7ra gene transcription (12,13,22,23), but very few of the mechanistic details of this process are known. Multiple signals can affect Il7ra transcription in T cells, including IL-7 (23), IL-2 (24), and TCR signaling that represses (13,25) and glucocorticoids (13,26) that induce Il7ra transcription. In addition, a few transcription factors have been identified that directly bind to and control Il7ra expression.…”
mentioning
confidence: 99%
“…Nuclear extract was prepared as described in ref. 35. Nuclear extract (5 g) was incubated for 20 min at room temperature with 2 ng of labeled oligonucleotide probe in 10 l of binding buffer [20 mM Tris⅐HCl (pH 7.5)/0.1 mM EDTA/4 mM DTT/40 mM NaCl/0.05% BSA/10% glycerol/0.125% Nonidet P-40) containing 1 g of poly(dI⅐dC).…”
mentioning
confidence: 99%